Enhanced piezoelectric response and thermal stability in (1 − x − y)(Na1/2Bi1/2)TiO3–y(K1/2Bi1/2)TiO3–xBaTiO3 ternary ferroelectric single crystals. (1st March 2016) - Yan, Hong; Zhang, Haiwu; Deng, Hao; Liu, Xing; Zhao, Xiangyong; Lin, Di; Li, Xiaobing; Luo, Haosu; Ko, Jae-Hyeon; Ahn, Chang Won
Abstract: The dielectric, ferroelectric and impedance properties of (1 − x − y)NBT–yKBT–xBT single crystals were investigated systematically. Our results demonstrate that the addition of KBT leads to enhanced piezoelectric response, thermal stability (e.g., depolarization temperature, Td ). The composition and temperature induced phase transformation mechanisms were characterized by using in-situ Raman spectra. The structure nature of improved electrical performance in (1 − x − y)NBT–yKBT–xBT ternary single crystals were discussed in detail.